2013
DOI: 10.1111/jfpp.12113
|View full text |Cite
|
Sign up to set email alerts
|

Drying Characteristics of Sea Cucumber (Stichopus japonicas Selenka ) Using Far Infrared Radiation Drying and Hot Air Drying

Abstract: Sea cucumber (Stichopus japonicus Selenka, SC) was dried using far infrared radiation drying (FIRD) and air drying (AD). The effect of the drying temperature of FIRD and AD on the drying rate of SC was investigated. Temperatures varied at 60, 70 and 80C, with a constant air velocity (13.2 m/s). Thin‐layer drying models were applied to describe the drying process of SC with FIRD and AD. The Midilli and Kucuk equation showed the best fit (R2 > 0.99). The effective moisture diffusivity (Deff) was estimated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…These products have to be rehydrated in cold water for more than 2 days and then subjected to a complex cooking procedure before consuming (Ferdouse, 2004;Ji, Kim, Dong, Pan, & Yoon, 2014). Most of sea cucumbers are processed into dried or salted products to facilitate storage and transport.…”
Section: Introductionmentioning
confidence: 99%
“…These products have to be rehydrated in cold water for more than 2 days and then subjected to a complex cooking procedure before consuming (Ferdouse, 2004;Ji, Kim, Dong, Pan, & Yoon, 2014). Most of sea cucumbers are processed into dried or salted products to facilitate storage and transport.…”
Section: Introductionmentioning
confidence: 99%
“…This process is carried out at 18°C–25°C for 72–96 hr (Li et al, ). However, this traditional method leads to problems such as long processing time, loss of many active compounds, inadequate removal of water, and contamination during the process (Duan, Zhang, Mujumdar, & Wang, ; Moon, Kim, Chung, Pan, & Yoon, ). Hot air drying, microwave drying, and freeze drying are alternatives to sun drying method.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is important to choose a drying method that will protect nutritive and bioactive substances in sea cucumbers, as well improve the quality of products (Li et al, ). In addition to these methods, researchers have used drying methods such as microwave freeze drying (Duan et al, ), dielectric drying (Duan, Zhang, Mujumdar, & Wang, ), combined electrohydrodynamic and vacuum freeze drying (Bai, Yang, & Huang, ), and far infrared radiation (Moon et al, ) to dry sea cucumbers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The E a values for PFP and RFP were 22.85 and 23.94 kJ mol −1 , respectively. The physical meaning of the E a value from the sample could be interpreted as the amount of energy required to transfer the moisture through the samples being dried (Moon et al ., ). In this study, the activation energy for the PFP was slightly lower than that of the RFP, which indicated that hot air dying of the PFP required slightly less energy than the RFP.…”
Section: Resultsmentioning
confidence: 97%